Corrosion behavioral studies on AA7075 surface hybrid composites tailored through friction stir processing. Issue 4 (7th May 2020) - Kandasamy, Suganeswaran; Rathinasamy, Parameshwaran; Nagarajan, Nithyavathy; Arumugam, Karthik; Rathanasamy, Rajasekar; Velu Kaliyannan, Gobinath
Abstract : Purpose: This paper aims to overcome the corrosion in AA7075 by incorporating the dual-reinforcements like Al2O3 and SiC through friction stir processing (FSP). In recent days, an automotive monocoque structure undergoes corrosion because of changes in environmental conditions. Design/methodology/approach: Surface hybrid composites (SHCs) of AA7075 with different weight ratios of Al2 O3 and SiC were fabricated at a rotating speed of 1000 rpm, traveling speed of 56 mm/min and tool tilt angle of 2º with two passes. Surface regions were observed using optical microscopy, and the potentiodynamic corrosion test was performed under a 3.5 per cent NaCl environment at room temperature. Then, the surface morphology analysis of corroded samples and their structural properties were also investigated through scanning electron microscopy (SEM), X-ray diffraction (XRD) and electron dispersive spectroscopy (EDS). Findings: Through FSP, an improved interface between the reinforced particles and the AA7075 base matrix was observed because of the severe plastic deformation. Potentiodynamic polarization tests confirmed that the AA7075 matrix with a higher concentration of Al2 O3 and a lower concentration of SiC (Al2 O3 – 75 per cent and SiC – 25 per cent) possesses a lower corrosion rate than other specimens. This result is because of the combined effect of stable passive film formation and the resistance produced by hard SiC particles. In addition, the formation of a stronger interface between the reinforcements and the base matrix impedes the NaCl solution attack. The SEM micrograph depicts the film crystallinity variations with an increase in Al2 O3 content. Debonding between the layers was observed on increasing the SiC content in the base matrix. XRD shows the peaks of reinforcing elements that influence the corrosion behavior. These observations suggest that the AA7075 reinforced with a higher concentration of Al2 O3 and a lower concentration of SiC through FSP affords a suitable solution for automotive monocoque applications. Originality/value: The corrosion rate has been identified for AA7075 SHCs with various concentrations of Al2 O3 and SiC and has been compared with that of the base metal and the friction stir processed specimen without reinforcement.